Social Network Development among Low‐Income Single Mothers: Potential for Bridging, Bonding, and Building. Issue 5 (December 2014) - Freeman, Amanda L.; Dodson, Lisa
<x xml:space="preserve">Abstract</x> This article explores the potential for community‐based social networks to help low‐income mothers manage responsibilities of work and family. This 3‐year ethnographic study examined the experiences of low‐income single mothers participating in an antipoverty program in Boston, Massachusetts, through 73 in‐depth interviews. The data refute the claim that bonds within the community hinder women in their attempts to move their families out of poverty. The authors observed benefits from social networks that emerged as a result of program participation in the following categories: practical support, emotional support, modeling and mentoring, and expansion of information resources. The authors also uncovered a new kind of social network formed among low‐income women who were actively pursuing a path out of poverty. These hybrid networks, building social networks, form among people who are straddling two worlds and, as such, are uniquely positioned to help one another.